Design and fabrication clothes rack - Muhammad Fauzie, Abu Bakar @ Nasir (2009)
Clothes rack is very important for people to hang their clothes. Every clothes rack has different use and specific use. There are some common problem can be detect at the clothes rack nowadays such as don’t have stopper, clothes easy to fall , heavyweight, only suitable for certain clothes, need many wheels, hard to cornering, not suitable for small area, cannot hang many things, unstable for heavy clothes like jacket, hard to manufacturer and expensive material. To reduce this problem, one new clothes rack will be development that have multi function and has not limited to do another task or job. This project is about design and fabricates a new product of clothes rack that has multifunction. The clothes rack multi use and easy assemble. It’s also must reduce the disadvantages of the clothes in the current market like have stopper, adjustable and easy manufacturer. As the conclusion, this project had achieves its entire objective successfully. This project was done around thirteen week included almost all steps of the report such as literature review, design, fabrication process and others.